2007
DOI: 10.1002/cbic.200600414
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Fluorescent Trimethoprim Derivatives for in vivo Protein Labeling

Abstract: The combined technologies of optical microscopy and selective probes allow for real-time analysis of protein function in living cells. Synthetic chemistry offers a means to develop specific, protein-targeted probes that exhibit greater optical and chemical functionality than the widely used fluorescent proteins. Here we describe pharmacokinetically optimized, fluorescent trimethoprim (TMP) analogues that can be used to specifically label recombinant proteins fused to E. coli dihydrofolate reductase (eDHFR) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 21 publications
1
101
0
Order By: Relevance
“…The characteristics of absorption, distribution, metabolism, and excretion are favorable with a relatively short blood half-life in humans, low serum protein binding (∼50%), and broad tissue distribution (24,25). Additionally, TMP is a well-studied chemical biology tool, is tolerant of large adorning chemical modifications, and is a well-known, clinically used antibiotic with antimicrobial activity against Gram-positive, Gram-negative, and some mycobacterial and parasitic species (10). In combination, these features suggested that TMP would satisfy many of the requirements of a good imaging agent and be worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of absorption, distribution, metabolism, and excretion are favorable with a relatively short blood half-life in humans, low serum protein binding (∼50%), and broad tissue distribution (24,25). Additionally, TMP is a well-studied chemical biology tool, is tolerant of large adorning chemical modifications, and is a well-known, clinically used antibiotic with antimicrobial activity against Gram-positive, Gram-negative, and some mycobacterial and parasitic species (10). In combination, these features suggested that TMP would satisfy many of the requirements of a good imaging agent and be worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…modifications including adaptation of fluorescent conjugates or heterodimer-related moieties (10,12). Briefly, TMP was converted to the phenol, the propyl-silyl-ether protecting group was added at the paraposition, the aromatic heterocyclic amine groups were bis-boc protected, and the propyl-mesylate was made.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic access to the TMP conjugates is straightforward. Modifications introduced to the para-methoxy position of the benzene ring minimally affect the binding to eDHFR, representing an ideal position for the linkage to fluorophores [18][19][20][21]. TMP itself has excellent cell permeability, as expected from its use as therapeutic agent.…”
Section: Noncovalent Protein Tagsmentioning
confidence: 99%
“…The 18 kDa monomeric eDHFR behaves well when expressed in mammalian cells, and TMP-fluorophore conjugates with standard linker and protection group chemistry show good cell permeability. Labeling of nuclear proteins, plasma membrane proteins, and cytoplasmic proteins have been demonstrated in various cell types, showing that the eDHFR-TMP receptor-ligand pair can be used as a robust noncovalent protein labeling system in living cells [17][18]. The TMP-tag is marketed as LigandLink by Active Motif (Carlsbad, CA).…”
Section: Noncovalent Protein Tagsmentioning
confidence: 99%